How Baitul Maal Wa Tamwil Solve Bad Financing During The Pandemic? - Sri Cahyaning Umi Salama; Nadia Nuryasmi Azizah (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2023)
During the pandemic, many MSMEs had to find many ways to survive. Most of the members of Baitul Maal wa Tamwil (BMT) are MSMEs, so BMTs must cooperate with MSMEs so that they can continue to make payment of financing installments smoothly so that BMT finances remain good. This study aims to analyze the strategies used by BMTs during a pandemic among MSME members. The method used is qualitative interviews centered on four BMTs in East Java. The results of the study show that there are three main strategies used by BMTs in dealing with MSMEs that have been affected by the pandemic, namely financing relief, additional capital, and business development. Financing relief is divided into three types, namely margin payments, rescheduling, and reconditioning.